High capacity variable friction damper based on band brake technology. (15th April 2016) - Downey, Austin; Cao, Liang; Laflamme, Simon; Taylor, Douglas; Ricles, James
Highlights: Proposal of a high performance, controllable, friction damping device. Friction damper is based on the mechanically robust double wrap band brake. Possible implementation within a structural system is discussed. A mathematical model is developed for the dampers hysteretic behavior. Laboratory verification of the damper demonstrates a damping force of 45 kN. Abstract: Implementation of high performance controllable damping devices can ameliorate cost-effectiveness of structural systems for mitigation of natural hazards. However, the applications of these damping systems are limited due to a lack of (1) mechanical robustness; (2) electrical reliability; and (3) large resisting force capability. To broaden the implementation of modern damping systems, a novel semi-active damping device is proposed. The device, termed Banded Rotary Friction Device (BRFD), has enhanced applicability compared to other proposed damping systems due to its cost-effectiveness, high damping performance, mechanical robustness, and technological simplicity. Its mechanical principle is based on a band brake, which results in a high amplification of the applied force while enabling a variable control force. The theoretical model of the BRFD is presented and experimentally verified by subjecting a prototype to various harmonic loads. Results show that the prototype BRFD is capable of a maximum force of 45 kN (10 kips) using only a 267 N (60 lb) actuation force, therefore providing a mechanical advantage of 169. A 3-stage dynamic model previously developed by the authors can successfully be used to model the dynamic behavior of the BRFD.